OPTIMALISASI PATROLI SATUAN SAMAPTA GUNA MENCEGAH TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI POLRESTABES SEMARANG - R. Ariel Andro Bramasta (Police Studies Review, 2022)
ABSTRACT OPTIMIZATION OF THE SAMAPTA PATROL TO PREVENT THE CRIMINAL ACTION OF WEIGHTING THEFT(CURAT) AT SEMARANG POLRESTABES R. Ariel Andro Bramasta, 18.091, radenarielandrobramasta@gmail.com Theft by weight is rampant in the jurisdiction of Semarang Police. Many people suffer losses due to the frequent occurrence of these crimes such as physical disturbances, economic losses, and psychological disorders. The formulation of the problem is how to carry out motorized vehicle patrols by the Semarang Polrestabes Samapta Unit, the factors that influence the motorized vehicle patrols of the Semarang Police Samapta Unit in preventing stealing crimes, and how to optimize the Semarang Porestabes Samapta Unit patrols in preventing stealing crimes. The author uses conceptual literature including management theory, crime prevention theory, organizational resource theory, patrol concept, and the concept of stealing crime. The research was conducted in February 2022 in the jurisdiction of Polrestabes Semarang, using the Field Research research method with a qualitative approach. Sources of data obtained from primary and secondary sources, interview data collection techniques, observation, and document review. The data analysis technique is data reduction, data presentation and drawing conclusions. From the results of the research and discussion, it can be concluded that the motorized vehicle patrol of the Semarang Police Samapta Unit in preventing the crime of stealing has gone quite well. However, there are still inhibiting factors for motor vehicle patrol activities in preventing the crime of stealing, namely the lack of personnel, the ability of patrol officers, and the lack of patrol support equipment. Suggestions from the authors are to maximize the strength of existing personnel, increase the ability of dialogical patrol officers, add infrastructure for motorized vehicle dialogue patrols, and increase supervision and control by utilizing technological developments.